Universities and Local Communities: Research, Training and Networking in the Field of Legality and Mafias, for the Right to Informed Knowledge - Zaccaria, Anna Maria; D’Alfonso, Stefano (Urbana, 2024)
This paper focuses on the commitment of Italian universities to training on legality and research on mafias. This commitment aims to guarantee students the right to informed knowledge, based on research and scientific reflection, of mafia phenomena. This is particularly important given that public opinion and the media often offer a distorted representation of organized crime phenomena, sometimes even dangerously downplaying their severity. The data underlying our reflections come from a Review of University Teaching and Research, which was created by the Interdisciplinary Laboratory of Research on Mafia and Corruption (LIRMAC) at the University Federico II. This review is a valuable resource that highlights the presence of a dedicated training offer, consisting of experts and research groups active within each university or across universities, which serve as expert channels of access to scientific knowledge of Mafia phenomena.